(untitled) (Oxford, New York, 1998)
The book explains the theoretical background to the notional, functional and communicative approaches to English language teaching. It deals with four main topics: the linguistics background, the background to teaching, applications and techniques, educational perspectives
Keywords: Language and languages; Study and teaching